The Use of Contingency Table Model of Two-way in Studying Sex Effect on the Famous Affection - Ahmed K. Ghannam; Laith A. Hamad (Tikrit Journal of Pure Science)
We study in this paper the using of the log-liner model in analyzing the categorical data in contingency table of two- way (rxc) , to find a better model which represents the data. This paper includes applied in healthy field. It has been studied sex effect on the affection of diarrhea which is caused by two kinds of parasite through nine syndrome.